Selection of lactic acid bacteria as a probiotic and evaluated its performance on gnotobiotic catfish Clarias sp. - Turnip, Enita Romasni; Widanarni, Widanarni,; Meryandini, Anja (Indonesian Society of Scientific Aquaculture (ISSA), 2018)
ABSTRACT This study aimed to select lactic acid bacteria (LAB) as a potential probiotic that producing anti‒microbial compounds in order to treat motile aeromonads septicemia diseases caused by Aeromonas hydrophila on catfish Clarias sp. and evaluated its performance on gnotobiotic catfish. The in vitro assay was done to select several LAB isolates based on antagonistic activity against pathogenic bacteria. The selected isolate was tested in vivo to observe their ability to improve growth performances of catfish. The study was conducted with five treatments consists of K‒ (normal catfish without addition probiotic, without challenge test), K+ (normal catfish without addition of probiotic, with challenge test), Np (normal catfish with addition of probiotic and challenge test), G (gnoto catfish without addition of probiotic, with challenge test), and Gp (gnoto catfish with addition of probiotic and challenge test). The results showed that the addition of Pediococcus pentosaceus E2211 as selected probiotic could increase survival rate, specific growth rate, and immune response towards infection of A. hydrophila. The best survival rate after challenge test was obtained in Np and Gp treatments (88.46%), followed by G treatment (65.38%), while the K+ was only 53.84%. The conclusion of this study was P. pentosaceus E2211 potentially used as a probiotic candidate for normal and gnotobiotic catfish. The presence of normal microflora with P. pentosaceus E2211 in Np treatment showed the best probiotic performance with daily growth rate 3.28%, feed conversion ratio 1.79, and total intestinal bacteria reached 108 CFU/mL significantly different from other treatments (P<0.05).Keywords: Aeromonas hydrophila, catfish, LAB, probiotic, screening ABSTRAKTujuan penelitian ini adalah menyeleksi bakteri asam laktat (BAL) sebagai probiotik potensial penghasil senyawa antimikrob guna menanggulangi penyakit motile aeromonad septicemia akibat Aeromonas hydrophila pada ikan lele Clarias sp. dan evaluasi kinerjanya pada ikan lele gnotobiotik. Pengujian in vitro dilakukan untuk menyeleksi beberapa isolat BAL sebagai kandidat probiotik berdasarkan aktivitas antagonis terhadap bakteri patogen. Isolat terpilih kemudian diuji in vivo untuk mengetahui kemampuannya dalam meningkatkan performa tumbuh ikan lele. Penelitian ini menggunakan rancangan acak lengkap dengan lima perlakuan, yaitu: K‒ (lele normal tanpa probiotik dan tanpa tanpa diuji tantang), K+ (lele normal tanpa probiotik dan diuji tantang), Np (lele normal diberi probiotik dan diuji tantang), G (lele gnoto tanpa probiotik dan diuji tantang), dan Gp (lele gnoto diberi probiotik dan diuji tantang). Hasil penelitian menunjukkan pemberian probiotik terpilih BAL Pediococcus pentosaceus E2211 mampu meningkatkan sintasan, laju pertumbuhan, dan respons imun ikan lele terhadap infeksi A. hydrophila. Sintasan terbaik pascauji tantang diperoleh pada perlakuan Np dan Gp yaitu sebesar 88,46%, diikuti perlakuan G sebesar 65,38%, sementara pada K+ hanya mencapai 53,84%. Kesimpulan dari penelitian ini ialah isolat BAL terpilih P. pentosaceus E2211 berpotensi sebagai kandidat probiotik untuk ikan lele normal dan lele gnotobiotik Clarias sp. Keberadaan mikroflora normal yang berasosiasi dengan P. pentosaceus E2211 pada perlakuan Np menunjukkan kinerja probiotik terbaik dengan nilai laju pertubuhan harian 3,28%, rasio konversi pakan 1,79 dan total bakteri usus mencapai 108 CFU/mL yang berbeda signifikan dibanding perlakuan lainnya (P<0,05).Kata kunci: A. hydrophila, BAL, ikan lele, probiotik, seleksi